The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006 Fortieth Asilomar Conference on Signals, Systems and Computers 2006
DOI: 10.1109/acssc.2006.354999
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Mapping of Image Registration Applications onto Configurable Hardware

Abstract: This paper develops techniques for mapping rigid image registration applications onto configurable hardware. Image registration is a computationally intensive domain that places stringent requirements on performance and memory management efficiency. Building on the framework of homogeneous parameterized dataflow, which provides an effective formal model for design and analysis of hardware and software for signal processing applications, we develop novel methods for representing and exploring the hardware desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
2
1

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…As a result, dataflow languages are increasingly popular. Their diversity, portability, and intuitive appeal have extended them to many application areas (e.g., see [4,9,22]). …”
Section: Introductionmentioning
confidence: 99%
“…As a result, dataflow languages are increasingly popular. Their diversity, portability, and intuitive appeal have extended them to many application areas (e.g., see [4,9,22]). …”
Section: Introductionmentioning
confidence: 99%
“…In order to accommodate the non-linear part of the coordinate transform, the actor connections have to be changed and new actors are introduced. As shown in Figure 3, instead of an input token being an individual coordinate, as in [13], we change it to represent the index of the sub-volume being processed. Here, by a "token" we mean a single datum that is transferred along a dataflow graph edge.…”
Section: Non Rigid Registration -Dataflow Modeling and Associated Anamentioning
confidence: 99%
“…We base our dataflow model for non-rigid registration on the dataflow model for the rigid registration as presented by Hemaraj et al in [13] (shown in Figure 2). Our dataflow model of the complete non-rigid registration system retains the remaining parts of the dataflow model for rigid registration as we separate the nonrigid algorithm into a linear part (global matrix multiplication) and a nonlinear part (B-splines interpolation).…”
Section: Non Rigid Registration -Dataflow Modeling and Associated Anamentioning
confidence: 99%
See 1 more Smart Citation
“…We present area and power calculations that characterize our proposed architectures. In terms of modeling methodology, we present useful refinements of our previous work on developing and applying novel data flow-based models and analysis methods of image registration applications [8]. These methods provide a framework for mapping and optimizing these applications onto embedded architectures.…”
Section: Introductionmentioning
confidence: 99%